Integrating molecular mechanisms and agronomic strategies for selenium biofortification in horticultural crops - Wang, Lixia; Shafiq, Fahad; Ding, Zheli; He, Yingdui (Frontiers in Plant Science, 2025)
Selenium (Se) is an essential element for humans. Biologically, it is incorporated into selenoproteins, which play crucial roles in thyroid hormone metabolism, immune system regulation, and antioxidant capacity. However, Se deficiency is a global health concern, affecting over 1 billion individuals, and the production of Se-fortified crops is inevitable. As a way forward, the biofortification of horticultural crops could improve Se nutrition. For plants, Se is a beneficial element, and crops exhibit significant variation in their ability to uptake Se which is also influenced by soil pH. Therefore, this review focuses on recent advancements in Se biofortification technologies for horticultural crops, including soil and foliar application methods, and explores the physiological processes and genetic mechanisms underlying Se uptake, transport, and assimilation in these crops. Furthermore, the effectiveness of different Se-salts in the regulation of Se levels in crops has been discussed, with special emphasis on the mechanisms involved.